The Slopeslides Potential Modeling Of Semarang City Roads - Vinsensius Priyo Wicaksono; Pratikso; Rinda Karlinasari (Fakultas Teknik Universitas Pasir Pengaraian, 2023)
The purpose of this study was to determine influencing parameters and dominant causes of roads-slope failures, and to determine the potential risk of roads-slope failures modeling in the Semarang City Region. This quantitative descriptive research uses primary an secondary data collection methods, identification of factors that cause landslides, observation of field conditions and processing of spatial data. Slope stability data collection to obtain a database of road slopes and selection of road sections in